L’economia del Profeta: la finanza islamica e i fondamenti religiosi del diritto islamico dei contratti Shari’ah Compliant (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. Premessa: l’Islam tra religione ed economia - 2. Dalla finanza al contratto islamico, tra vincolo e libertà: alla ricerca di una teoria generale dei contratti - 3. L’etica islamica dei contratti: divieto di ribà e divieto di ghàrar - 4. Operatività delle attività della banca islamica e contrattualistica commerciale Shari’ah Compliant - 5. I contratti di tipo partecipativo: “mudàraba” e “mushàraka” - 6. (segue) Tipologie di mudàraba - 7. Cenni conclusivi e prospettive future.The Prophet's Economy: Islamic Finance and the Religious Foundations of Islamic Law of Shari'ah Compliant ContractsABSTRACT: The growing presence of Muslim believers in Europe has increasingly led to heated debates also at the doctrinal level. Legal and economic literature, particularly, has recently emphasised the importance that inclusive, effective and efficient financial regulation can have on the degree of integration of the Islamic communities present in non-Muslim contexts. Since the Shari'ah dictates a series of behavioural rules in different sectors of the believer’s life, the Koran and the narratives of the Prophet (hadith) offer a series of prescriptions also in economic matters. With the aim of outlining the religious and juridical reasoning of the so-called halal economic dimension, this paper first examines the economic principles of Islamic finance: the prohibition of ribà (interest), the prohibition of ghàrar (uncertainty) and that of maysìr (speculation). It then provides a recognition aimed at finding a general theory of Islamic contracts. Finally, it reconstructs the discipline of the mudàraba and musharàka participatory contracts. These two forms of contracts represent a product of Islamic finance widely used in banking-financial practice and considered by Islamic legal schools to be totally in conformity with the Word of Allah. They are therefore instruments of comparison particularly interesting as well as useful for the Italian legal system. They can represent a flywheel for the integration of Muslims in the social fabric, and at the same time, an antidote to the unstable European economic panorama.